2016
DOI: 10.1016/j.ebiom.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Variation of 46 Innate Immune Genes Evaluated for their Contribution in Pneumococcal Meningitis Susceptibility and Outcome

Abstract: Pneumococcal meningitis is the most common and severe form of bacterial meningitis. Early recognition of the pathogen and subsequent innate immune response play a vital role in disease susceptibility and outcome. Genetic variations in innate immune genes can alter the immune response and influence susceptibility and outcome of meningitis disease.Here we conducted a sequencing study of coding regions from 46 innate immune genes in 435 pneumococcal meningitis patients and 416 controls, to determine the role of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Subsequently, the complement system is activated, leading to massive release of anaphylotoxins and chemotaxis and activation of neutrophils [11]. Genetic variants in complement system, TLR and IL-1R signaling pathways, and the M-TOR pathway have been identified to be associated with outcome in pneumococcal meningitis [7, 9, 1215]. Inhibition of the final common pathway in the complement cascade has been identified as target for adjunctive treatment for experimental pneumococcal meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the complement system is activated, leading to massive release of anaphylotoxins and chemotaxis and activation of neutrophils [11]. Genetic variants in complement system, TLR and IL-1R signaling pathways, and the M-TOR pathway have been identified to be associated with outcome in pneumococcal meningitis [7, 9, 1215]. Inhibition of the final common pathway in the complement cascade has been identified as target for adjunctive treatment for experimental pneumococcal meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that CARD8 rs2043211 was found to be associated with susceptibility to gout [58], nodular melanoma [59], and decreased risk of ankylosing spondylitis [60]. Nonetheless, CARD8 rs2043211 could not predict the occurrence or progression of coronary artery diseases [61] or the susceptibility and outcome of meningitis [62]. The CARD8 rs2043211 (C10X) polymorphism leads to a nonfunctional truncated CARD8 and subsequently more active inflammasome and prolonged inflammation [38, 63].…”
Section: Discussionmentioning
confidence: 99%
“…SNPs leading to a loss of the human CD22 protein have not been described so far. Systematic GWAS research on pneumococcal pneumonia susceptibility are lacking in the human, due to the difficulties in obtaining sufficient numbers of defined human subjects [24][25][26] and to the complex trait in susceptibility to infection, which is modulated by the individual's environment, age and gender [27]. Here we have described that the cd22 locus as a novel strong susceptibility locus for pneumococcal disease in mice.…”
Section: Plos Pathogensmentioning
confidence: 91%